PROTAC® technology and potential for its application in infection control - M. A. Zakharova; M. V. Chudinov (Тонкие химические технологии)
Objectives. To describe the pharmaceutical technology of controlled degradation of protein molecules (PROTAC®, Proteolysis Targeting Chimera), approaches to the design of the PROTAC® molecule, methods of ligand and linker selection and synthesis, as well as the application of this technology in dealing with a variety of diseases and the possible limitations of its use.Results. The review covers 77 sources, mostly from 2020–2023. The review outlines the principle of PROTAC® technology: the construction of a chimeric molecule consisting of three fragments. One fragment specifically binds to the biotarget, another recruits the proteolytic system of the host cell, and the third binds them together. The main areas of the current development of the technology are described herein, as well as the opportunities and limitations of chimeric molecules in the fight against different types of infectious diseases.Conclusion. The potential to use PROTAC® technology to combat cancer as well as neurodegenerative, autoimmune, and infectious diseases is shown.